Indonesian Business Competition Law post the enactment Government Regulation in Lieu of Law on Job Creation Regulation into Law - Gusliadi, Gusliadi; Purnama, Nur Aziziyah; Pamungkas, Rizaldi Tri; Muhammad Azimuddin Mohamed (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This study aims to find out the development of business competition law in Indonesia as stipulated in Law Number 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition and its impact on the dynamics of business competition in Indonesia after the enactment of Law Number 6 of 2023 on Stipulation of Government Regulation in Lieu of Law (Government Regulation in Lieu of Law) Number 2 of 2022 concerning Job Creation into Law. This study uses a normative method with a statute approach and a library research approach. The formulation of the problem in this study is the development of business competition law in Indonesia after the enactment of the Government Regulation in Lieu of Law on Job Creation into Law and the impact of the enactment of Law Number 6 of 2023 on the dynamics of business competition in Indonesia. The results showed that the Business Competition Law in Indonesia experienced the first change in terms of substance after the enactment of Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. These changes then led to a shift in the dynamics of the Competition Procedure Law, which was considered regressed.